The Self and the Other: A Further Reflection on Buddhist–Christian Dialogue - Zhang, Shiying (Religions, 2024)
The dialogue between and comparative research into Christianity and Buddhism theoretically involve the issues of self and other. Faced with the cultural reality of religious diversity, theologies of religions provide four modes of dialogue through which Christianity can interface with religious others. The exploration of the infinite and transcendent traits of otherness in contemporary phenomenological philosophy, as well as the emphasis on differences in postmodern philosophy, contributes to maintaining a clear awareness of otherness and self-identity in the Buddhist–Christian dialogue. Following the dialogical path in comparative theology, which leads one out of oneself, into the other, and back into oneself, in experimental Buddhist-Christian dialogue activities, both Christianity and Buddhism figure as the self and the other. If they openly accept each other’s otherness and heterogeneity, view each other as mirrors, and criticize and reflect on themselves, then creative insights into themselves will ultimately be generated. Their selves will be rediscovered, and their understanding and expression will be updated. Reflecting on the Buddhist–Christian dialogue from four aspects, namely, ultimate realism, cosmology, ethics, and religious ideals, can eliminate some misunderstandings and deepen both parties’ understandings of themselves and others.